High-strength PE bar and preparation method thereof

Through the synergistic action of modified graphene filler and nanoactivated calcium carbonate, a geometallographic structure is formed, which solves the problem of insufficient mechanical properties and creep resistance of traditional PE materials under high load and dynamic environments, and significantly improves the strength and stability of PE rods.

CN119875233AInactive Publication Date: 2025-04-25GANZHOU HENGXIN PLASTIC IND CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510387077.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-04-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional PE materials are difficult to meet the mechanical properties and creep resistance requirements under high load or dynamic environments, and the effect of existing graphene strengthening PE is limited.

Method used

Modified graphene filler is used to introduce the end epoxy structure by reacting epoxy propylene oxide with alkylenol, and alkylation is modified by the edge activity of graphene oxide. Combined with nano-activated calcium carbonate as an ultramicro filler, a geochamber structure is formed to enhance the mechanical properties of PE.

Benefits of technology

The tensile strength, bending modulus and creep resistance of PE rods are significantly improved, and an interpenetrating network structure is formed to inhibit molecular chain slippage and maintain good toughness and stability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a high-strength PE bar and a preparation method thereof, and belongs to the technical field of polymer composite materials. The PE bar is prepared from the following components in percentage by weight: 10 to 15 percent of modified graphene filler, 5 to 8 percent of ultramicro filler, 4 to 5.5 percent of HDPE (High-Density Polyethylene) grafted maleic anhydride, 1 to 1.3 percent of lubricant, 0.04 to 0.05 percent of antioxidant and the balance of PE resin, according to the modified graphene filler, epoxy chloropropane and alkyl enol react to introduce an end epoxy structure, the characteristic that the edge activity of graphene oxide is high is utilized, an epoxidation modifier and graphene oxide are subjected to ring opening grafting to obtain an edge alkylation matrix, and then terminal thiophenol is introduced for modification through alkenyl addition introduced by 1, 4-benzene dithiol and the edge alkylation matrix. In a high-temperature processing process, a thiophenol-terminated structure is oxidized to form a disulfide bond, and a spatial geocell in which graphene sheet layers and disulfide organic structures are alternated is formed in a PE matrix, so that the PE matrix is reinforced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer composite materials, and in particular relates to a high-strength PE rod and a preparation method thereof. Background Art

[0002] Polyethylene (PE) rods are widely used in the fields of construction, machinery and geotechnical engineering due to their light weight, corrosion resistance and easy processing. However, the mechanical properties (such as tensile strength and flexural modulus) and creep resistance under long-term load of traditional PE materials are difficult to meet the requirements of high load or dynamic environment. In recent years, graphene has been regarded as an ideal nano-reinforced filler due to its excellent mechanical properties (theoretical tensile strength 130GPa, modulus 1TPa) and ultra-high specific surface area. However, the effect of directly using graphene to strengthen PE in the existing technology has significant limitations.

[0003] The graphene surface is inert and only combines with the PE molecular chain through physical adsorption. The interface shear strength is low and the load transfer efficiency is insufficient. In addition, the edges of the graphene sheets are sharp, which easily forms stress concentration points in the PE matrix and causes microcracks. The existing technology can only improve its dispersibility through surface treatment, and the strengthening of the PE system is far lower than the theoretical effect. Summary of the invention

[0004] In order to solve the technical problems mentioned in the background technology, the object of the present invention is to provide a high-strength PE rod and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A high-strength PE rod comprises: 10-15wt% of modified graphene filler, 5-8wt% of ultrafine filler, 4-5.5wt% of HDPE grafted maleic anhydride, 1-1.3wt% of lubricant and 0.04-0.05wt% of antioxidant, and the balance is PE resin.

[0006] The modified graphene filler is prepared by the following method: Step A1: premix alkyl enol, triethylamine and dimethyl sulfoxide, heat to 40-60°C, add epichlorohydrin and stir to react for 2.5-4h, then add sodium hydroxide and continue to heat to 100-120°C and stir to react for 1.2-1.8h. After the reaction is completed, remove dimethyl sulfoxide by vacuum rotary evaporation, cool and wash with water, remove the water phase and vacuum dry to obtain an epoxidation modifier.

[0007] Furthermore, the feed ratio of alkyl enol, epichlorohydrin, triethylamine, sodium hydroxide and dimethyl sulfoxide is 0.1 mol: 0.11-0.13 mol: 5-8 mL: 1.6-2.4 g: 45-60 mL, and triethylamine provides weak alkaline conditions to promote the ring opening of epichlorohydrin and alkyl enol, and then the ring is closed under high temperature and strong alkalinity to form epoxy end-capping.

[0008] Furthermore, the alkyl enol is one of 7-octenol, undecenol and octadecenol, and different alkyl chain lengths are matched with the diameter of the graphene sheet to obtain composite materials with different strengths and toughnesses.

[0009] Step A2: premix the epoxidation modifier, hexadecyltrimethylammonium bromide and acetone, add graphene oxide and stir to disperse, heat to 50-60°C, stir and reflux for 3.5-5h, and remove acetone by rotary evaporation after the reaction to obtain an edge alkylated matrix.

[0010] Furthermore, the feed ratio of graphene oxide, epoxidation modifier, hexadecyltrimethylammonium bromide and acetone is 50g:10-15mmol:0.12-0.15g:150-200mL, and hexadecyltrimethylammonium bromide is used as a phase transfer catalyst to promote the ring opening of the epoxidation modifier and the enriched oxygen-containing groups at the edge of the graphene oxide sheet, graft the epoxidation modifier to the edge of the graphene oxide, and introduce olefinic modification at the same time.

[0011] Furthermore, the average sheet diameter of graphene oxide is 1-10 μm, at which sheet diameter good dispersibility is maintained, and a stable geocell structure is easily formed between graphene oxide sheets.

[0012] Step A3: Premix 1,4-benzenedithiol, azobisisobutyronitrile and toluene, heat to 55-65°C, and apply 600-800 mW / cm 2 The modified graphene filler was obtained by UV irradiation, adding the edge alkylated matrix and ultrasonic oscillation reaction for 1.5-2h. After the reaction, the precipitate was centrifuged and washed with ethanol and dried.

[0013] Furthermore, the feed ratio of the edge alkylation substrate, 1,4-benzenedithiol, azobisisobutyronitrile and toluene is 50g:15-20mmol:20-30mg:140-180mL. Under photoinitiation and free radical initiation, excess 1,4-benzenedithiol is added to the alkenyl group introduced by the edge alkylation substrate to introduce terminal thiophenol modification.

[0014] Furthermore, the ultrafine filler is nano-activated calcium carbonate, which has good dispersibility and synergistically strengthens the geocell formed by the modified graphene filler.

[0015] A method for preparing a high-strength PE rod, specifically comprising: Step S1: premixing the modified graphene filler, HDPE grafted maleic anhydride, lubricant and PE resin, plasticizing and mixing at 180±5° C., adding ultrafine filler and antioxidant, extruding and granulating to obtain a composite masterbatch; Step S2: The composite masterbatch is injection molded to form a PE rod.

[0016] Beneficial effects of the present invention: The invention discloses a modified graphene filler suitable for a PE system. The modified graphene filler is prepared by reacting epichlorohydrin with an alkyl enol to introduce a terminal epoxy structure, namely, an epoxidation modifier. The high edge activity of graphene oxide is utilized to open the ring of the epoxidation modifier and graphene oxide, and an alkyl chain-containing alkenyl group is introduced into the edge of the graphene sheet layer for modification, namely, an edge alkylation matrix is ​​obtained. Then, 1,4-benzenedithiol is added to the alkenyl group introduced into the edge alkylation matrix to introduce a terminal thiophenol modification. Compared with a traditional graphene-based filler, the invention introduces an organic group to modify the graphene filler according to the edge activity characteristics of graphene oxide. The modification weakens the splitting effect of lamellar graphene in the PE matrix, and under the modification of alkyl chains, the compatibility of graphene sheets with the PE matrix is ​​improved. In addition, during high-temperature processing, the terminal thiophenol structure is oxidized to form a disulfide bond, and a spatial geocell of alternating graphene sheets and disulfide organic structures is formed in the PE matrix, which is entangled with the PE macromolecular chain to form an interpenetrating network, inhibiting the slip of the molecular chain and strengthening the composite system. At the same time, the organic alkyl long chain in the geocell structure provides a certain toughness buffer, which can maintain good toughness compared with the existing filler-reinforced PE materials. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0018] Example 1: Preparation of high-strength PE rods. The specific implementation method is as follows: 1. Preparation of modified graphene filler Step A1: pre-mix 7-octenol, triethylamine and dimethyl sulfoxide, heat to 40°C, add epichlorohydrin, stir and react at 60rpm for 4h, then add sodium hydroxide and continue to heat to 100°C and stir and react for 1.8h, wherein the feed ratio of 7-octenol, epichlorohydrin, triethylamine, sodium hydroxide and dimethyl sulfoxide is 0.1mol:0.11mol:5mL:1.6g:45mL. After the reaction is completed, dimethyl sulfoxide is removed by vacuum rotary evaporation, cooled and washed with water, the aqueous phase is removed and vacuum dried to obtain an epoxidation modifier.

[0019] Step A2: pre-mix the epoxidation modifier, hexadecyltrimethylammonium bromide and acetone, add graphene oxide, stir and disperse at 600 rpm, heat to 50°C, stir and reflux at 40 rpm for 5 hours, wherein graphene oxide uses XF002-2 type raw material with an average flake diameter of 3 μm, and the feed ratio of graphene oxide, epoxidation modifier, hexadecyltrimethylammonium bromide and acetone is 50 g:10 mmol:0.12 g:150 mL. After the reaction, remove acetone by rotary evaporation to obtain an edge alkylated matrix.

[0020] Step A3: Premix 1,4-benzenedithiol, azobisisobutyronitrile and toluene, heat to 55°C, and apply 600 mW / cm 2 The mixture was irradiated with UV, and an edge alkylated matrix was added and reacted with 20kHz ultrasonic oscillation for 2h, wherein the feed ratio of edge alkylated matrix, 1,4-benzenedithiol, azobisisobutyronitrile and toluene was 50g:15mmol:20mg:140mL. After the reaction, the precipitate was centrifuged and washed with ethanol and dried to obtain a modified graphene filler.

[0021] 2. Preparation of PE rods Ingredients: modified graphene filler 10wt%, homemade in this embodiment; ultrafine filler 8wt%, LP-600 type nano-activated calcium carbonate; HDPE grafted maleic anhydride 4wt%, W1H type commercially available raw material; lubricant 1.3wt%, K0060F type polyethylene wax; antioxidant 0.05wt%, antioxidant B225; the balance is PE resin, HDPE-2200J type resin raw material.

[0022] Step S1: premixing modified graphene filler, HDPE grafted maleic anhydride, lubricant and PE resin, feeding from the main feeding port of a twin-screw extruder, plasticizing and mixing at 180±5° C., mixing ultrafine filler and antioxidant and feeding from the side feeding port, extruding and granulating to obtain a composite masterbatch.

[0023] S2: The composite masterbatch is injection molded at a melt temperature of 200±10°C and an injection pressure of 50±2MPa. The mold is then cooled and demolded to obtain a PE rod.

[0024] Example 2, preparation of high-strength PE rods, the specific implementation method is as follows: 1. Preparation of modified graphene filler Step A1: pre-mix octadecenol, triethylamine and dimethyl sulfoxide, heat to 60°C, add epichlorohydrin, stir and react at 90rpm for 2.5h, then add sodium hydroxide and continue to heat to 120°C and stir and react for 1.2h, wherein the feed ratio of octadecenol, epichlorohydrin, triethylamine, sodium hydroxide and dimethyl sulfoxide is 0.1mol:0.13mol:8mL:2.4g:60mL. After the reaction is completed, dimethyl sulfoxide is removed by vacuum rotary evaporation, cooled and washed with water, the aqueous phase is removed and vacuum dried to obtain an epoxidation modifier.

[0025] Step A2: Take the epoxidation modifier, hexadecyltrimethylammonium bromide and acetone for premixing, then add graphene oxide, stir and disperse at 600 rpm, heat to 60°C, stir and reflux at 60 rpm for 3.5 hours, wherein the graphene oxide uses XF021 type raw material with an average flake diameter of 8 μm, and the feed ratio of graphene oxide, epoxidation modifier, hexadecyltrimethylammonium bromide and acetone is 50 g:15 mmol:0.15 g:200 mL. After the reaction, the acetone is removed by rotary evaporation to obtain an edge alkylated matrix.

[0026] Step A3: Premix 1,4-benzenedithiol, azobisisobutyronitrile and toluene, heat to 65°C, and apply 800 mW / cm 2 The mixture was irradiated with UV, and an edge alkylated matrix was added and reacted with 25kHz ultrasonic oscillation for 1.5h, wherein the feed ratio of edge alkylated matrix, 1,4-benzenedithiol, azobisisobutyronitrile and toluene was 50g:20mmol:30mg:180mL. After the reaction, the precipitate was centrifuged and washed with ethanol and dried to obtain a modified graphene filler.

[0027] 2. Preparation of PE rods Ingredients: 15wt% modified graphene filler, homemade in this embodiment; 5wt% ultrafine filler, LP-600 nano-activated calcium carbonate; 5.5wt% HDPE grafted maleic anhydride, W1H type commercially available raw material; 1wt% lubricant, K0060F type polyethylene wax; 0.04wt% antioxidant, antioxidant B225; the remainder is PE resin, HDPE-2200J type resin raw material.

[0028] Step S1: premixing modified graphene filler, HDPE grafted maleic anhydride, lubricant and PE resin, feeding from the main feeding port of a twin-screw extruder, plasticizing and mixing at 180±5° C., mixing ultrafine filler and antioxidant and feeding from the side feeding port, extruding and granulating to obtain a composite masterbatch.

[0029] S2: The composite masterbatch is injection molded at a melt temperature of 200±10°C and an injection pressure of 50±2MPa. The mold is then cooled and demolded to obtain a PE rod.

[0030] Example 3, preparation of high-strength PE rods, the specific implementation method is as follows: 1. Preparation of modified graphene filler Step A1: pre-mix undecenol, triethylamine and dimethyl sulfoxide, heat to 50°C, add epichlorohydrin, stir and react at 60rpm for 3.2h, then add sodium hydroxide and continue to heat to 110°C and stir and react for 1.6h, wherein the feed ratio of undecenol, epichlorohydrin, triethylamine, sodium hydroxide and dimethyl sulfoxide is 0.1mol: 0.12mol: 7mL: 2.2g: 50mL. After the reaction is completed, dimethyl sulfoxide is removed by vacuum rotary evaporation, cooled and washed with water, the aqueous phase is removed and vacuum dried to obtain an epoxidation modifier.

[0031] Step A2: Take the epoxidation modifier, hexadecyltrimethylammonium bromide and acetone for premixing, then add graphene oxide, stir and disperse at 600 rpm, heat to 50°C, stir and reflux at 60 rpm for 4 hours, wherein the graphene oxide uses XF002-2 type raw material with an average flake diameter of 3 μm, and the feed ratio of graphene oxide, epoxidation modifier, hexadecyltrimethylammonium bromide and acetone is 50 g:12 mmol:0.13 g:180 mL. After the reaction, the acetone is removed by rotary evaporation to obtain an edge alkylated matrix.

[0032] Step A3: Premix 1,4-benzenedithiol, azobisisobutyronitrile and toluene, heat to 60°C, and apply 600 mW / cm 2 The mixture was irradiated with UV, and an edge alkylated matrix was added and reacted with 20kHz ultrasonic oscillation for 2h, wherein the feed ratio of edge alkylated matrix, 1,4-benzenedithiol, azobisisobutyronitrile and toluene was 50g:18mmol:25mg:160mL. After the reaction, the precipitate was centrifuged and washed with ethanol and dried to obtain a modified graphene filler.

[0033] 2. Preparation of PE rods Ingredients: 13wt% modified graphene filler, homemade in this embodiment; 7wt% ultrafine filler, LP-600 nano-activated calcium carbonate; 5wt% HDPE grafted maleic anhydride, W1H type commercially available raw material; 1.2wt% lubricant, K0060F type polyethylene wax; 0.04wt% antioxidant, antioxidant B225; the remainder is PE resin, HDPE-2200J type resin raw material.

[0034] Step S1: premixing modified graphene filler, HDPE grafted maleic anhydride, lubricant and PE resin, feeding from the main feeding port of a twin-screw extruder, plasticizing and mixing at 180±5° C., mixing ultrafine filler and antioxidant and feeding from the side feeding port, extruding and granulating to obtain a composite masterbatch.

[0035] S2: The composite masterbatch is injection molded at a melt temperature of 200±10°C and an injection pressure of 50±2MPa. The mold is then cooled and demolded to obtain a PE rod.

[0036] Example 4, preparation of high-strength PE rods, the specific implementation method is as follows: 1. Preparation of modified graphene filler Step A1: pre-mix undecenol, triethylamine and dimethyl sulfoxide, heat to 55°C, add epichlorohydrin, stir and react at 90rpm for 3h, then add sodium hydroxide and continue to heat to 120°C and stir and react for 1.5h, wherein the feed ratio of undecenol, epichlorohydrin, triethylamine, sodium hydroxide and dimethyl sulfoxide is 0.1mol:0.12mol:6mL:2g:55mL. After the reaction is completed, dimethyl sulfoxide is removed by vacuum rotary evaporation, cooled and washed with water, the aqueous phase is removed and vacuum dried to obtain an epoxidation modifier.

[0037] Step A2: Take the epoxidation modifier, hexadecyltrimethylammonium bromide and acetone for premixing, then add graphene oxide, stir and disperse at 600 rpm, heat to 55°C, stir and reflux at 60 rpm for 4.2 h, wherein the graphene oxide uses XF021 type raw material with an average flake diameter of 8 μm, and the feed ratio of graphene oxide, epoxidation modifier, hexadecyltrimethylammonium bromide and acetone is 50 g:15 mmol:0.15 g:180 mL. After the reaction, the acetone is removed by rotary evaporation to obtain an edge alkylated matrix.

[0038] Step A3: Premix 1,4-benzenedithiol, azobisisobutyronitrile and toluene, heat to 65°C, and apply 700 mW / cm 2 The mixture was irradiated with UV, and an edge alkylated matrix was added and reacted with 25kHz ultrasonic oscillation for 1.8h, wherein the feed ratio of edge alkylated matrix, 1,4-benzenedithiol, azobisisobutyronitrile and toluene was 50g:18mmol:20mg:150mL. After the reaction, the precipitate was centrifuged and washed with ethanol and dried to obtain a modified graphene filler.

[0039] 2. Preparation of PE rods Ingredients: 12wt% modified graphene filler, homemade in this embodiment; 8wt% ultrafine filler, LP-600 nano-activated calcium carbonate; 4.8wt% HDPE grafted maleic anhydride, W1H type commercially available raw material; 1.1wt% lubricant, K0060F type polyethylene wax; 0.05wt% antioxidant, antioxidant B225; the remainder is PE resin, HDPE-2200J type resin raw material.

[0040] Step S1: premixing modified graphene filler, HDPE grafted maleic anhydride, lubricant and PE resin, feeding from the main feeding port of a twin-screw extruder, plasticizing and mixing at 180±5° C., mixing ultrafine filler and antioxidant and feeding from the side feeding port, extruding and granulating to obtain a composite masterbatch.

[0041] S2: The composite masterbatch is injection molded at a melt temperature of 200±10°C and an injection pressure of 50±2MPa. The mold is then cooled and demolded to obtain a PE rod.

[0042] Comparative Example 1, referring to Example 4, the modified graphene filler was replaced with the same amount of ultrafine filler, and the rest of the implementation process was exactly the same.

[0043] Comparative Example 2, referring to Example 4, the modified graphene filler was replaced with the same amount of XF006 type thiol graphene, and the rest of the implementation process was exactly the same.

[0044] Comparative Example 3, referring to Comparative Example 2, the amount of thiolated graphene is increased to 20wt%, and the balance is adjusted to 100wt% by PE resin, and the rest of the implementation process is exactly the same.

[0045] Samples were taken from the PE rods prepared as above, and tensile tests were performed according to ASTM D638-2022, bending tests were performed according to ASTM D790-2017, impact tests were performed according to ASTM D256-2023, and bending creep tests were performed according to ASTM D2990-2017. The specific test results are shown in Table 1: Table 1 Tensile strength / MPa Flexural modulus / GPa <![CDATA[Impact strength / kJ·m -2 > Bending creep / % Example 1 31.0 1.94 11.5 2.04 Example 2 29.3 2.27 10.1 1.32 Example 3 34.7 2.09 11.9 1.70 Example 4 33.5 2.17 12.4 1.55 Comparative Example 1 25.3 1.35 12.8 5.83 Comparative Example 2 21.9 1.62 8.6 4.26 Comparative Example 3 26.4 1.88 5.4 3.49 It can be seen from the test results in Table 1 that the PE rod prepared in the embodiment has excellent toughness and very low bending creep, and has excellent stability as a rod.

[0046] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0047] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A high-strength PE rod, characterized in that: The components are: 10-15wt% of modified graphene filler, 5-8wt% of ultrafine filler, 4-5.5wt% of HDPE grafted maleic anhydride, 1-1.3wt% of lubricant and 0.04-0.05wt% of antioxidant, and the balance is PE resin; The modified graphene filler is prepared by the following method: Step A1: premixing an alkyl enol, triethylamine and dimethyl sulfoxide, heating to 40-60° C., adding epichlorohydrin and stirring to react for 2.5-4 hours, then adding sodium hydroxide and continuing to heat to 100-120° C. and stirring to react for 1.2-1.8 hours. After the reaction is completed, dimethyl sulfoxide is removed by vacuum rotary evaporation, and after cooling, water is added to wash, the aqueous phase is removed and vacuum drying is performed to obtain an epoxidation modifier; Step A2: premix the epoxidation modifier, hexadecyltrimethylammonium bromide and acetone, add graphene oxide, stir and disperse, heat to 50-60°C, stir and reflux for 3.5-5h, and remove acetone by rotary evaporation after the reaction to obtain an edge alkylated matrix; Step A3: Premix 1,4-benzenedithiol, azobisisobutyronitrile and toluene, heat to 55-65°C, and apply 600-800 mW / cm 2 The modified graphene filler was obtained by UV irradiation, adding the edge alkylated matrix and ultrasonic oscillation reaction for 1.5-2h. After the reaction, the precipitate was centrifuged and washed with ethanol and dried.

2. A high-strength PE rod according to claim 1, characterized in that: The feed ratio of alkyl enol, epichlorohydrin, triethylamine, sodium hydroxide and dimethyl sulfoxide is 0.1 mol: 0.11-0.13 mol: 5-8 mL: 1.6-2.4 g: 45-60 mL.

3. A high-strength PE rod according to claim 2, characterized in that: The alkyl enol is one of 7-octenol, undecenol and octadecenol.

4. A high-strength PE rod according to claim 2, characterized in that: The feeding ratio of graphene oxide, epoxidation modifier, hexadecyltrimethylammonium bromide and acetone is 50 g: 10-15 mmol: 0.12-0.15 g: 150-200 mL.

5. A high-strength PE rod according to claim 4, characterized in that: The average sheet diameter of graphene oxide is 1-10 μm.

6. A high-strength PE rod according to claim 4, characterized in that: The feed ratio of the edge alkylation substrate, 1,4-benzenedithiol, azobisisobutyronitrile and toluene is 50 g: 15-20 mmol: 20-30 mg: 140-180 mL.

7. A high-strength PE rod according to claim 1, characterized in that: The ultrafine filler is nano-active calcium carbonate.

8. A method for preparing a high-strength PE rod according to any one of claims 1 to 7, characterized in that: Specifically: Step S1: premixing modified graphene filler, HDPE grafted maleic anhydride, lubricant and PE resin, plasticizing and mixing at 180±5° C., adding ultrafine filler and antioxidant, extruding and granulating to obtain a composite masterbatch; Step S2: The composite masterbatch is injection molded to form a PE rod.

Citation Information

Patent Citations

  • Graphene enhanced polyethylene pipe and preparation method thereof

    CN109054147A

  • Modified graphene plastic and preparation method

    CN110452463A

  • Modified high-density polyethylene pipe and production process thereof

    CN116410532A

  • Use of high-aspect-ratio graphene materials as additives for thermoplastic materials

    EP3770207A1

  • Use of high-aspect-ratio graphene materials as additives for thermoplastic materials

    WO2019180292A1